2005
DOI: 10.1152/jn.00924.2004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intrinsic Properties of Pyramidal Neurons in Adult Rat S1 During Cortical Reorganization

Abstract: Hickmott, Peter W. Changes in intrinsic properties of pyramidal neurons in adult rat S1 during cortical reorganization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…5 C and D). Reduced intrinsic excitability has also been observed previously after whisker deprivation (37) and peripheral denervation (38). The reduced firing rate was associated with increased spike width (ANOVA P = 0.012) but no change in spike threshold (Fig.…”
Section: Pw-evoked Excitation and Inhibitionsupporting
confidence: 83%
“…5 C and D). Reduced intrinsic excitability has also been observed previously after whisker deprivation (37) and peripheral denervation (38). The reduced firing rate was associated with increased spike width (ANOVA P = 0.012) but no change in spike threshold (Fig.…”
Section: Pw-evoked Excitation and Inhibitionsupporting
confidence: 83%
“…Indeed Shoykhet and Simons (2008) recently reported that the tuning properties of barrel cortex develop within a similar time frame (P14 -P28), consistent with the maturation of excitatory and inhibitory synaptic connections (Blue and Parnavelas 1983;White et al 1997). On the other hand, the membrane and response properties of individual cortical neurons are fully mature by P14 (Maravall 2004) and change very little in adult (Hickmott 2005) or senescent rats (Burke and Barnes 2006).…”
Section: Barrel Neurons In Vitro Versus In Vivomentioning
confidence: 99%